A Selective Bioreduction of Toxic Heavy Metal Ions from Aquatic Environment by Saccharomyces cerevisiae - A. M. Rahatgaonkar; N. R. Mahore (E-Journal of Chemistry)
The need to remove or recover metal ions from industrial wastewater has been established in financial as well as environmental terms. This need has been proved financially in terms of cost saving through metal reuse or sale and environmentally as heavy metal toxicity can affect organisms throughout the food chain, including humans. Bioremediation of heavy metal pollution remains a major challenge in environmental biotechnology. Current removal strategies are mainly based on bioreduction of Co++, Ni++, Cu++ and Cd++ to their metallic forms by Saccharomyces cerevisiae in buffered aqueous solution. The rate of biotransformation was significantly influenced by pH of aqueous solution, concentration of biomass and hardness of water. All reaction conditions were optimized and maximum reduction of Co++, Cd++, Ni++ and Cu++ were observed as 80%, 63%, 50%, and 44% respectively. Unreacted Co++, Cd++, Ni++metal ions were extracted by 8-hydroxyquinoline and Cu++ by diethylthio carbamate in CHCl3 at different pH. Furthermore, the concentrations of unreacted metal ions were established spectrophotometrically.